2000
DOI: 10.1002/1097-0215(20001115)88:4<626::aid-ijc17>3.0.co;2-q
|View full text |Cite
|
Sign up to set email alerts
|

Sequences of cytotoxic T-lymphocyte epitopes in the Epstein-Barr virus (EBV) nuclear antigen-3B gene in a Japanese population with or without EBV-positive lymphoid malignancies

Abstract: Latent infection antigens of EBV, including EBV nuclear antigens (EBNAs) and latent membrane proteins, are expressed in latently infected and immortalized B cells but work as target antigens for host cytotoxic T‐lymphocyte (CTL) responses in an HLA class I–restricted manner. Among these latent antigens, the immunodominant CTL epitopes in EBNA3B (EBNA3B 399–408 and EBNA3B 416–424) are well characterized. Mutations and strain differences in these sequences, compared to the prototype A sequence, reduce CTL respon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…Therefore, as summarized in , only 3 of 31 Japanese virus strains showed evidence of A11 epitope mutation, whereas Chinese virus isolates (established in earlier work, Midgley et al , 2003a) were very frequently mutated, with a range of different sequence changes evident in different isolates. Note that two earlier studies of Japanese EBV strains, amplifying just across the IVT/AVF epitope region and using fresh or archived biopsy tissues, have also reported low frequencies of sequence change, affecting one or other epitope in 20–25 % of samples studied (Chu et al , 1999; Kanno et al , 2000). Thus, the predominance of A11 epitope-loss mutants appears to be a specific feature of contemporary Chinese virus strains and not a general feature of Asian virus isolates.…”
Section: Discussionmentioning
confidence: 83%
“…Therefore, as summarized in , only 3 of 31 Japanese virus strains showed evidence of A11 epitope mutation, whereas Chinese virus isolates (established in earlier work, Midgley et al , 2003a) were very frequently mutated, with a range of different sequence changes evident in different isolates. Note that two earlier studies of Japanese EBV strains, amplifying just across the IVT/AVF epitope region and using fresh or archived biopsy tissues, have also reported low frequencies of sequence change, affecting one or other epitope in 20–25 % of samples studied (Chu et al , 1999; Kanno et al , 2000). Thus, the predominance of A11 epitope-loss mutants appears to be a specific feature of contemporary Chinese virus strains and not a general feature of Asian virus isolates.…”
Section: Discussionmentioning
confidence: 83%
“…The EBV gene expression profile of PAL is usually Latency III. It has been suggested that the EBV-transformed B cells at the site of chronic inflammation are able to escape host immune surveillance and grow out through several mechanisms, for example involving production of cellular IL-10, an immunosuppressive cytokine [ 100 , 101 ], autocrine growth promotion via the IL-6 and IL-6 receptor pathway [ 102 ], downregulation of MHC class I expression [ 103 ] and mutation of immunodominant T cell epitopes in EBNA3B [ 104 ]. In addition, microarray analysis has identified interferon-inducible 27 (IFI27) as one of the most differentially expressed genes in PAL compared to regular DLBCL [ 105 ].…”
Section: Diffuse Large B Cell Lymphomamentioning
confidence: 99%
“…Production of immunosuppressive cytokine IL-10 by PAL cells, decreased or lost expression of HLA class I molecules in PAL cells, or mutation of the CTL-epitope in EBNA3B might work as mechanisms for escape of PAL cells from CTL. 19,20) Cell lines established from PAL, including the present ones, showed very complex karyotypes. Two PAL cell lines (OPL-1, -2) reported previously by us 14) also showed complex karyotypes with many numerical and chromosomal abnormalities.…”
Section: Discussionmentioning
confidence: 70%